2008
DOI: 10.1007/s10545-008-0914-x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of a citrin‐deficient patient at the early stage of adult‐onset type II citrullinaemia with arginine and sodium pyruvate

Abstract: Citrin deficiency is a common congenital metabolic defect not only in East Asian populations but also in other populations around the world. It has been shown that although liver transplantation is ultimately required in many patients to prevent neurological decompensation associated with hyperammonaemia, arginine is effective in lowering ammonia in hyperammonaemic patients, and a high-protein low-carbohydrate diet may provide some benefit to infants in improving failure to thrive. In the present study, the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
38
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(40 citation statements)
references
References 20 publications
(25 reference statements)
2
38
0
Order By: Relevance
“…Our previous study also showed that Pyr ameliorates the deficit in ureogenesis in the perfused liver [16]. Our present results are consistent with the finding that treatment with Na-Pyr improves the clinical outcome citrin-deficient patients [35,36]. Although further work is needed to clarify the mechanism(s) in which Pyr improves liver metabolism in citrin-deficient patients, our present results further support the effectiveness of Pyr as a treatment regime.…”
Section: Discussionsupporting
confidence: 92%
“…Our previous study also showed that Pyr ameliorates the deficit in ureogenesis in the perfused liver [16]. Our present results are consistent with the finding that treatment with Na-Pyr improves the clinical outcome citrin-deficient patients [35,36]. Although further work is needed to clarify the mechanism(s) in which Pyr improves liver metabolism in citrin-deficient patients, our present results further support the effectiveness of Pyr as a treatment regime.…”
Section: Discussionsupporting
confidence: 92%
“…For CTLN2, clinical benefit has been demonstrated with liver transplantation (Saheki et al 2010). Recently, a favorable result was reported in one patient with therapy using sodium pyruvate and arginine under the low carbohydrate formula (Mutoh et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…throughout life including growth retardation and hypoglycemia in infancy, fatty liver, hypertriglyceridemia, pancreatitis and hepatocellular carcinoma [5][6][7][8][9][10][11][12][13][14][15][16][17]. Citrin has been identified as the hepatic isoform of the mitochondrial aspartate-glutamate carrier (AGC) [18], known to participate in the cytosolic synthesis of proteins, nucleotides and urea through supplying mitochondrial-derived aspartate.…”
mentioning
confidence: 99%